The Roles of Size and Size Difference in Australian and Chinese Inter-firm Collaborations - Yu (Aimee) Zhang; Zhiming Cheng; Charles Harvie (Australasian Accounting, Business and Finance Journal, 2013)
There has been considerable debate on the contribution and significance of firm size to the establishment, operation and success of business collaboration. One important source of this debate arises from differing definitions of firm size used in previous research. This paper uses firm size categories and size differences between collaborating firms to examine their contribution to the formation and performance of inter-firm collaboration in Australia and China. Both qualitative case study and quantitative data analyses are adopted in this paper. Results from both the qualitative case study and quantitative study in Australia and China show that size plays a significant positive role in the formation and performance of business collaboration. Firms prefer collaborating with larger partners. Bigger firms are more likely to achieve success collaborations. However, size difference plays a negative role in business collaboration. Collaborating with a bigger partner makes it harder to succeed. On the other hand, size and size difference play very different roles in performance and outcomes of business collaboration in different countries. This paper compares the roles of firm size and size difference in Australian and Chinese inter-firm collaboration. The results provide important strategic implications for business managers, industry regulators, and policy decision makers regarding international business collaboration.
Keywords: Collaboration; Size; Size Difference; Australia; China